(untitled) (Світ фінансів, 2017)
Пруський О. С. Монетарні аспекти інтеграції України в європейський валютний простір. Розглянуто об’єктивні передумови європейської монетарної інтеграції, обґрунтовано механізм функціонування європейської валютної системи з позиції теорії оптимальних валютних зон. Проаналізовано досвід країн – нових членів Європейського Союзу в адаптації їхніх фінансово-кредитних систем до європейських стандартів, вказано на проблемні місця у даному процесі. Наголошено на важливості реалізації ефективної грошово-кредитної та валютної політики Національного банку України, що повинні сприяти прискоренню гармонійного входження України у європейський економічний простір. Prusciy O. Monetary aspects of Ukrainian integration to the European currency space. It is considered objective preconditions of the European monetary integration, it is proved the mechanism of functioning of the European currency system from a position of the theory of optimum currency areas. Experience of the countries – new members of the European Union in branch of adaptation of their financial systems-credit to the European standards is analysed, is specified problem places in the given process. Importance of realization of effective monetary and currency policy of the National bank of Ukraine is marked, that must be instrumental in acceleration of harmonious entrance of Ukraine in European economic space.